2020
DOI: 10.1088/1402-4896/abbc9e
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric, impedance and modulus spectroscopy of Pb(Zr0.52−x Ce x Ti0.48)O3 (x = 0.00, 0.10) ferroelectric ceramics

Abstract: Lead zirconate titanate (PZT) ceramics of morphotropical phase boundary (MPB) composition shows enhanced physical properties on modification with suitable ions. In this work, Pb(Zr0.52-xCe x Ti0.48)O3, x = 0.00, 0.10 (PZCT) ferroelectric ceramics have been synthesized by solid state synthesis route. The ferroelectric nature of samples is confirmed by their transition of phase from the ferroelectric phase to the paraelectric phase. At 1 MHz frequency, the Curie temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…With rise in temperature, the conductivity of all samples in increasing indicating the presence of peaks at higher temperatures. These peaks correspond to the dielectric relaxation peaks that can observed near Curie temperature region [7,23]. The increment in conductivity with rise in temperature suggests the semiconducting nature i.e.…”
Section: Variation Of Ac Conductivity With Temperaturementioning
confidence: 66%
See 2 more Smart Citations
“…With rise in temperature, the conductivity of all samples in increasing indicating the presence of peaks at higher temperatures. These peaks correspond to the dielectric relaxation peaks that can observed near Curie temperature region [7,23]. The increment in conductivity with rise in temperature suggests the semiconducting nature i.e.…”
Section: Variation Of Ac Conductivity With Temperaturementioning
confidence: 66%
“…The inorganic oxides of 99.9% purity were used to prepare the samples of Pb(Zr 0.52-x Y x Ti 0.48 )O 3 (x = 0.00, 0.10 and Y = Mn/Ce). The complete procedure and process parameters are similar to that, which have been reported elsewhere [22][23].…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…Lots of work has been reported by lots of researchers, on the solid state synthesized PZT ceramics. In one of the work [4], PZT of 52/48 ratio has been prepared by modifying it with cerium. It was observed that the relative permittivity of the PZT has been enhanced.…”
Section: Fig2 Flow Chart Of Solid State Synthesismentioning
confidence: 99%
“…It is concluded that the interesting electrical properties can be induced by PZT, when it is synthesized through solid state mixing of powders. For more understanding on this method, bibliography can be referred [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Fig2 Flow Chart Of Solid State Synthesismentioning
confidence: 99%